Structure−Property relationships in nanocomposites based on cyanate ester resins and 1-heptyl pyridinium tetrafluoroborate ionic liquid. (18th July 2018) - Vashchuk, A.; Rios de Anda, A.; Starostenko, O.; Grigoryeva, O.; Sotta, P.; Rogalsky, S.; Smertenko, P.; Fainleib, A.; Grande, D.
Abstract: Novel thermosetting systems based on cyanate ester resins (CERs) have been created through the polycyclotrimerization reaction of dicyanate ester of bisphenol E (DCBE) in the presence of different amounts of 1-heptyl pyridinium tetrafluoroborate [HPyr][BF4 ] Ionic Liquid (IL). A significant accelerating effect on the curing kinetics of DCBE was found by FTIR analysis. The reaction mechanism for the [HPyr][BF4 ]-catalyzed polycyclotrimerization of DCBE was newly proposed via the formation of a [CN] δ+ –[HPyr] δ− complex as a key intermediate. Structure–properties relationships for the thermostable CER/IL networks were investigated by using DSC, DMTA, dielectric spectroscopy, tensile testing, quasi-dc measurements ( I-V characteristics), and TGA. All the nanocomposites showed excellent thermal stability up to 300 °C, indicating the formation of a densely crosslinked network even at high IL content (40 wt%), and they could be used at high temperatures above their T g without significant thermal degradation. Nanoscale phase separation led to the creation of ionic channels within the CER matrix to ensure photosensitivity properties. Graphical abstract: Image 1 Highlights: [HPyr][BF4 ] acts both as a catalyst and a structure-directing agent increasing free volume in CER-based nanocomposites. Nanoscale phase separation leads to the creation of ionic channels within the CER matrix to ensure photosensitivity properties. Nanocomposite materials can be used at high temperatures above their T g without significant thermal degradation.